2017
DOI: 10.1186/s13717-017-0107-3
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic factors influencing household forest dependency in Chobe enclave, Botswana

Abstract: Introduction: Human dependence on forests is a multifaceted phenomenon. The degree of reliance on forests varies geographically, overtime and across communities. These dynamics underpin the importance of understanding the determinants of household reliance on forests for the long-term sustainable forest management and conservation. This paper presents an analysis of socio-economic determinants on the level of household forest dependency in Chobe enclave, Botswana. The study hypothesised that the level of house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 30 publications
(53 reference statements)
7
40
1
Order By: Relevance
“…This is likely associated with the availability of environmental products suggesting that these originate from inside the PA. This finding is consistent with other studies indicating that proximity to forests increases the reliance of households on forest environmental products (Baiyegunhi et al, 2016;Garekae et al, 2017).…”
Section: Household Socio-economic Factors Determining Environmental Rsupporting
confidence: 93%
See 3 more Smart Citations
“…This is likely associated with the availability of environmental products suggesting that these originate from inside the PA. This finding is consistent with other studies indicating that proximity to forests increases the reliance of households on forest environmental products (Baiyegunhi et al, 2016;Garekae et al, 2017).…”
Section: Household Socio-economic Factors Determining Environmental Rsupporting
confidence: 93%
“…This could be due to higher profitability of off-farm activities compared to harvesting environmental products. Other studies have also found that income from off-farm activities such as employment and other regular paid activities significantly reduced households' environmental reliance (Mulenga et al, 2011;Tieguhong & Nkamgnia, 2012;Garekae et al, 2017).…”
Section: Household Socio-economic Factors Determining Environmental Rmentioning
confidence: 98%
See 2 more Smart Citations
“…Their study observed that despite the various changes in both internal and external policies, population growth, competition among households and more profitable economic opportunities still threaten forest resources dependence. Garekae et al (2017) studied the level of household forest dependency using a range of socioeconomic factors around the Chobe Forest Reserve of Botswana. Their study found age and education to significantly influence household forest resource dependence.…”
Section: Economic Drivers and Household Forest Resources Dependencementioning
confidence: 99%